Synthesis and trifluoromethylation of allylsilanes - Galicia Lopez, O (2013)
The first part of this thesis presents a novel approach for synthesising enantioenriched cyclic allylsilanes via asymmetric ring-closing metathesis (ARCM). The second part of this thesis focuses on the reactivity of allylsilanes in electrophilic trifluoromethylation under transition metal and photoredox catalysis. Chapter 1 provides a general introduction to existing methods for preparing compounds containing Si-stereogenic centres. The motivation for using ARCM to form Si-stereogenic centres is discussed. To set the stage for this work, the development of olefin metathesis as a tool in organic synthesis is briefly summarised. Chapter 2 describes the synthesis of various prochiral silicon-containing trienes and their reactivity in Ru-, Mo- and W-catalysed ring-closing metathesis. . Following extensive screening of chiral catalysts, few catalysts were identified that enabled selective ARCM to access Si-stereogenic products in up to 98% ee. A systematic investigation of the relationship between the structure of the starting material (i.e., hydrocarbon chain length, steric and electronic properties of the silicon substituents) and the resulting efficacy in ARCM was undertaken, the results from these experiments are discussed. Importantly, this study represents the first example in which ARCM has been successfully used to desymmetrise prochiral substrates to form a new chiral Si centre (Scheme 1). Chapter 3 provides a general introduction to the field of trifluoromethylation, with a special focus on recent applications of transition metal catalysts in Csp2–CF3 and Csp3–CF3 bond formation. A myriad of effective nucleophilic, electrophilic and radical trifluromethylating reagents have been developed during the past several years; the properties of these reagents and their compatibility with various modes of catalysis are summarised to provide a context for the second part of this thesis research. Chapter 4 presents two novel methods for effecting trifluoromethylation of allylsilanes . First, it was discovered that the combination of an electrophilic trifluoromethlyating reagent and a copper catalyst effectively mediated trifluoromethylation of allylsilanes. The silicon substituent was crucial for improving the nucleophilicity of the substrate and dictating the regioselectivity of the Csp3–CF3 bond-forming step. With this method, alkyl or aryl substitution at the β-position of the allylsilane was critical for reactivity. Second, in a complementary study, it was found that copper could be replaced by a ruthenium photocatalyst and visible light. This latter method allowed for trifluoromethylation of substrates that were ineffective with copper catalysis. Mechanistic studies of both reaction systems were undertaken, and plausible reaction pathways for both reactions are proposed. Chapter 5 gives full experimental procedures and characterisation data for all compounds.